How does salinity influence habitat selection and growth in juvenile American eels Anguilla rostrata?. Issue 2 (21st January 2015) - Boivin, B.; Castonguay, M.; Audet, C.; Pavey, S. A.; Dionne, M.; Bernatchez, L.
<x xml:space="preserve">Abstract</x> The influence of salinity on habitat selection and growth in juvenile American eels Anguilla rostrata captured in four rivers across eastern Canada was assessed in controlled experiments in 2011 and 2012. Glass eels were first categorized according to their salinity preferences towards fresh (FW), salt (SW) or brackish water (BW) and the growth rate of each group of elvers was subsequently monitored in controlled FW and BW environments for 7 months. Most glass eels (78–89%) did not make a choice, i.e. they remained in BW. Salinity preferences were not influenced by body condition, although a possible role of pigmentation could not be ruled out. Glass eels that did make a choice displayed a similar preference for FW (60–75%) regardless of their geographic origin but glass eels from the St Lawrence Estuary displayed a significantly higher locomotor activity than those from other regions. Neither the salinity preferences showed by glass eels in the first experiment nor the rearing salinities appeared to have much influence on growth during the experiments. Elvers from Nova Scotia, however, reached a significantly higher mass than those from the St Lawrence Estuary thus supporting the hypothesis of genetically (or epigenetically) based differences for growth between A. rostrata from different origins. These results provide important ecological knowledge for the sustained exploitation and conservation of this threatened species.